Norleucine, a natural occurrence in a novel ergot alkaloid gamma-ergokryptinine - Cvak, L; Jegorov, A; Sedmera, P; Císarová, I; Cejka, J; Kratochvíl, B; Pakhomova, S (Amino acids, 2005)
A novel natural peptide ergot alkaloid gamma-ergokryptinine containing norleucine has been isolated from ergot sclerotia of the field-growing parasitic fungus Claviceps purpurea CCM 8059. Its structure was deduced from the NMR and mass spectral data. The final structural proof was provided by the crystal structure determination, which is the first X-ray structure of a natural Nle-containing secondary metabolite. The conformations of three ergopeptinines: gamma-ergokryptinine, ergoladinine, and alpha-ergokryptinine were compared.
Keywords: ergotaminy; Ergot Alkaloids; Claviceps; nukleární magnetická rezonance biomolekulární; Ergotamines; Norleucine; krystalizace; Nuclear Magnetic Resonance, Biomolecular; norleucin; námelové alkaloidy; Crystallization